Prudential regulation, the "credit crunch" and the ineffectiveness of monetary policy: Evidence from Japan - Wako Watanabe (Osaka University, Institute of Social and Economic Research (ISER), 2004)
The underlying causes of sharp declines in bank lending during recessions in large developed economies, as exemplified by the U.S. in the early 1990s and Japan in the late 1990s, are still being debated due to a lack of any convincing identification strategy of the supply side capital-lending relationship with lending demand. This paper is a first attempt to construct a strong instrument for bank capital from empirical observation of the banks' behavioral changes in the past and to estimate the impact of capital adequacy on the lending supply. The implications of prudential regulation and the ineffectiveness of a loose monetary policy are discussed based on the micro evidence presented.
Keywords: C21; E50; G21; 330; credit crunch; prudential regulation; bank lending channel; instrumental variable; Kreditmarkt; Bankenkrise; Geldpolitik; Bankenregulierung; Geldpolitische Transmission; Japan; Instrumentalvariablen-Schätzmethode